Extension of holomorphic mappings for few moving hypersurfaces - Si, Duc Quang (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We prove the big Picard theorem for holomorphic curves from a punctured disc into P^n(C) with n + 2 hypersurfaces. We also prove a theorem on the extension of holomorphic mappings in several complex variables into a submanifold ofP^n(C) with several moving hypersurfaces.